SOSIALISASI PENGGUNAAN APLIKASI ADUAN ELEKTRONIK MAKSIMUM KOMPLAIN (EMAK) PADA DINAS SOSIAL KABUPATEN PRINGSEWU - Dwi Yana Ayu Andini; Zulkifli Zulkifli; Andi Mulyono; Panji Bintoro; M. Galih Ramaputra; Joko Triloka (Jurnal Abdimas Bina Bangsa, 2023)
The social service is a government agency tasked with improving the quality of social welfare for individuals, groups and communities. One of the mandates of the social service is the service of social complaints in the regions, especially in Pringsewu District. Currently the complaint system still uses a manual system. This caused an obstacle, namely the slow service of complaints, so EMAK (Maximum Complaint Electronic Application) was created to speed up and improve the handling of complaints related to the need for social services, especially in the administrative area of the Pringsewu social service. The methods used in the EMAK application are interview methods, observation methods and literature reviews. This application is designed with a simple layout to facilitate the use of social services manager, just enter according to the section, users can directly access the relevant application. The Emak application was developed to make it easier for social services to process information on public complaints